Challenges in CEFR adoption: teachers' understanding and classroom practice / Nurul Farehah Mohamad Uri - Mohamad Uri, Nurul Farehah (Universiti Teknologi MARA, 2023)
CEFR has been extensively adopted in many countries including Malaysia. Currently at the third phase of the implementation, the concept of CEFR and the applicability is not new to most teachers. Over the years, numerous local studies have been conducted to discover the real situation faced by both teachers and students who are directly affected by the government's decision to replace the previous syllabus with the new CEFR aligned English syllabus. This study was conducted with the objectives of investigating the challenges encountered by English teachers on understanding CEFR and the potential challenges faced by the teachers in CEFR classroom practice in the adoption process. A panel member of the English Language Standard and Quality Council (ELSQC) and 331 school teachers participated in this study. Survey and in-depth interview were employed for data gathering. Computer software such as NVivo and SPSS were used for data analysis. Results show that most teachers lack understanding especially on the adoption of the framework. Moreover, classroom practice is a real challenge to the teachers because the imported CEFR-aligned textbooks are causing additional workload due to adapt them to the local context. Preparing and designing their own CEFR aligned teaching materials based on the new syllabus is another challenge of classroom practice for the teachers.